Etv6 activates vegfa expression through positive and negative transcriptional regulatory networks in Xenopus embryos - Lei Li (Nature Portfolio, 2019)
How vegfa expression is transcriptionally regulated in vivo is unclear. Here, the authors demonstrate that the ETS transcription factor Etv6 acts as a repressor and an activator of two direct regulators of vegfa expression (foxo3 and klf4, respectively) to control blood formation in Xenopus.